2016
DOI: 10.1038/ncomms13620
|View full text |Cite
|
Sign up to set email alerts
|

Stacked antiaromatic porphyrins

Abstract: Aromaticity is a key concept in organic chemistry. Even though this concept has already been theoretically extrapolated to three dimensions, it usually still remains restricted to planar molecules in organic chemistry textbooks. Stacking of antiaromatic π-systems has been proposed to induce three-dimensional aromaticity as a result of strong frontier orbital interactions. However, experimental evidence to support this prediction still remains elusive so far. Here we report that close stacking of antiaromatic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 36 publications
4
94
0
1
Order By: Relevance
“…The Hückel 20p-electron antiaromatic characteristics of 5,15dioxaporphyrin were revealed by 1 HNMR spectroscopy, and its electronic structure was characterized experimentally by UV/Vis/NIR absorption and MCD spectroscopies and theoretically by TDDFT,N ICS,a nd GIMIC calculations. 5,15-Dioxaporphyrin is stable under ambient conditions, whereas it forms a b,b-linked dimer upon oxidation instead of attaining 18p-electron aromatic oxidation state.S ince it is recently reported that antiaromatic norcorrole exhibits unique conducting properties arising from the small HOMO-LUMO gap [37] and its laminated dimer attains three-dimensional aromaticity, [38] the extension of such research to 5,15-dioxaporphyrin is of significant interest, and investigations along these lines is being intensively pursued in our laboratory.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The Hückel 20p-electron antiaromatic characteristics of 5,15dioxaporphyrin were revealed by 1 HNMR spectroscopy, and its electronic structure was characterized experimentally by UV/Vis/NIR absorption and MCD spectroscopies and theoretically by TDDFT,N ICS,a nd GIMIC calculations. 5,15-Dioxaporphyrin is stable under ambient conditions, whereas it forms a b,b-linked dimer upon oxidation instead of attaining 18p-electron aromatic oxidation state.S ince it is recently reported that antiaromatic norcorrole exhibits unique conducting properties arising from the small HOMO-LUMO gap [37] and its laminated dimer attains three-dimensional aromaticity, [38] the extension of such research to 5,15-dioxaporphyrin is of significant interest, and investigations along these lines is being intensively pursued in our laboratory.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In such 1D bulk materials, tuning inter‐monomer distance alternation patterns, which may be tuned by chemical modifications of monomers and/or physical perturbations, are shown to be one of the important factors to enhance the bulk phase NLO susceptibility ,. Antiaromatic porphyrin 1B with appropriate substituent groups can also form up to trimers with interesting geometric and electronic structures by self‐assembly . Exploration of open‐shell‐character‐based molecular design strategies for tuning the aggregations of antiaromatic molecules like porphyrins is therefore expected to contribute to further progress in expression of unique functionalities in open‐shell materials.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that norcorrolatonickel(II) 1 , a readily obtainable air‐stable antiaromatic 16‐π‐electron tetrapyrrolic porphyrinoid, can be effectively functionalized by means of diverse substitution, addition, insertion, or dimerization reactions. Amination of the macrocycle followed by oxidative annulation has been recently shown to be an effective way to fuse aromatic rings .…”
Section: Methodsmentioning
confidence: 99%